1991
DOI: 10.1007/bf00202405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a break-prone structure in the 9q1 heterochromatic region

Abstract: The unusual behaviour of the 9q1 human chromosome region is studied in various conditions. In controls with normal chromosomes 9, del(9q1) is the most frequent spontaneously occurring deletion. This deletion is highly inducible by melphalan, an S phase-dependent alkylating agent. This may correspond to the uncovering of pre-existing DNA breaks in this region. In a 46,XX,9qh+ control, melphalan does not induce deletions any more efficiently than in donors with normal chromosomes 9. In a 46,XY,inv(9) (p11q1205) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In addition, all the 9qh region was on the 3q9q translocation chromosome suggesting that the breakpoint on chromosome 9 must be at 9qll very near to the centromere. This is consistent with the propensity to breakage reported for 9qh in different conditions.9 10 In conclusion, the study of this patient emphasises how the combination of classical cytogenetic techniques with the resolution power of FISH allows the definition with more accuracy of the breakpoints and the origin of centromeres in this type of translocation.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, all the 9qh region was on the 3q9q translocation chromosome suggesting that the breakpoint on chromosome 9 must be at 9qll very near to the centromere. This is consistent with the propensity to breakage reported for 9qh in different conditions.9 10 In conclusion, the study of this patient emphasises how the combination of classical cytogenetic techniques with the resolution power of FISH allows the definition with more accuracy of the breakpoints and the origin of centromeres in this type of translocation.…”
Section: Discussionsupporting
confidence: 88%
“…In these disorders, genes responsible for cell cycle regulation and/or DNA repair are defective; as a result, affected individuals have a higher risk of malignancies [Varon et al, 1998; Neff et al, 1999; Dokal, 2000; Kraemer, 2000; Zhou and Elledge, 2000; van Gent et al, 2001]. In addition, chromosomal instability resulting in hemizygous subclones via somatic recombination was suggested by Mamuris et al [1991], who observed that the majority of cells with deletions in the heterochromatic region in both controls and a 9qh+ donor were at 9q12. If this occurred, however, phenotypic consequences of the abnormal gene would probably be manifested in heterozygous carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The rearrangement could have involved sister chromatids of 9p. However, breakage of chromosome 9 appears to occur most frequently in the 9q1 region [Mamuris et al, 1991]. Thus, it is possible that breakage could have occurred in the short arm of a chromosome 9, bearing an inversion of the 9qh heterochromatic segment.…”
Section: Discussionmentioning
confidence: 99%